Globalización neoliberal y antropodiversidad: (tres) propuestas para promover la paz y el diálogo intercultural - Aguiló Bonet, Antoni Jesús (Nómadas. Critical Journal of Social and Juridical Science, 2009)
Departing from the definition of neoliberal globalization as a western localism that contains a new form of cultural imperialism, this paper aims at making a critical and descriptive analysis of three approaches that, despite their differences in content and style, seek to address the risks that neoliberal globalization involves for human diversity. These proposals include: the global ethics of Hans Küng, the intercultural translation of Boaventura de Sousa Santos and the critical and skeptical attitude of Michel de Montaigne.